Technology-Based Assessment for Children with Special Needs: Improving Accessibility and Accuracy in Inclusive Education Environments - Susanti, Dewi Juwita; Mirnawati, Mirnawati; Amka, Amka; Widodo, Agus Pratomo Andi; T, Etna Anjani; Rizqina, Aulia; Rahmawati, Nor; Bonafita, Raberria (FKIP ULM, 2024)
This study aims to evaluate the effectiveness of technology-based assessment applications in identifying and assessing the needs of learners with special needs in inclusive schools. Using a mixed methods design, this study involved 40 respondents consisting of teachers and parents of children with special needs in inclusive schools in Banjarbaru, with data collection through surveys, observations and in-depth interviews. The results showed that the technology-based assessment application made it easier to understand the needs of children with disabilities and plan more effective interventions, with 85% of respondents (teachers and parents) finding it easy to use. 78% of respondents felt that the app helped them to identify children's cognitive, emotional, social and physical abilities more accurately than manual methods. Use of the app also improved the efficiency of the learning process, with 70% of observations indicating regular use by teachers and 60% by parents. This study highlights the importance of additional training and improved technology infrastructure to maximize the benefits of this app. In conclusion, this study shows that technology can effectively overcome the challenges of assessing children with disabilities and support the development of inclusive education policies in Indonesia.